Hazard assessment of the Chilean tsunami of September 16th, 2015 for Costa Rica - Chacón Barrantes, Silvia (2016)
A Mw 8.3 earthquake took place in Chile on September 16th, 2015 causing a local tsunami. As a consequence, this earthquake prompted the National Tsunami Monitoring System (SINAMOT) in Costa Rica to conduct a tsunami hazard assessment in order to provide the National Emergency Committee (CNE) with recommendations on how to respond locally to the tsunami. This event represented an exercise to implement SINAMOT Standard Operating Procedures (SOPs) and to use local forecast tools for tsunami heights and currents for the first time, which produced successful results. This paper describes the forecast conducted by SINAMOT, the tools used for the hazard assessment, and the tsunami records in Costa Rica. Along Costa Rica’s continental shores, the tsunami was recorded only by tide gauge instruments, as predicted by SINAMOT. This paper has an operative approach and shows the results in the same format as they are used for decision making processes during the event.